PENGARUH KETERAMPILAN KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEMBERDAYAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN PANDEGLANG - Risma Eka Desiyani; Uli Wildan Nuryanto; Sri Wasiatul Hasanah (Jurusan Manajemen FEB UHO, 2025)
This study aims to determine the effect of work skills, work discipline, and work environment on employee performance at the Community Empowerment and Village Government Service of Pandeglang Regency. The research method used is based on data collection techniques, so this study was conducted using a quantitative approach by distributing questionnaires. The population in the study were all employees totaling 63 people, with sampling using saturated samples totaling 63 people, with multiple linear regression analysis techniques. The results of this study indicate that partially work skills, work discipline, and work environment have a significant effect on employee performance at the Community Empowerment and Village Government Service of Pandeglang Regency, while simultaneously work skills, work discipline, and work environment have a significant effect on employee performance at the Community Empowerment and Village Government Service of Pandeglang Regency